Restoring Autonomy out of Context. Selective Heritagisation of the Drama Theatre in Veliky Novgorod - Ksenia Litvinenko (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
This article considers the politics of heritagisation in relation to late Soviet built environments within a contemporary authoritarian context. It examines the imaginaries underpinning the 2020 competition for the renovation of the Novgorod Drama Theatre in North-West Russia (1970–1987), designed by Vladimir Somov of the Giproteatr Institute and completed as part of a state-sponsored theatre-building program. The article argues that, by drawing upon project-related drawings from Somov’s private archive, the competition organisers sought to aesthetically amplify aspects of his creative vision, such as an unrealised lighting solution, the concept of a “total theatre,” and the flexible auditorium. These efforts aimed to restore the architect’s autonomy through renovation. Simultaneously, certain elements of the late Soviet building industry and subsequent maintenance were presented as expendable, allegedly hindering the full realization of the architect’s individual creative aspirations. Consequently, the theatre’s renovation concept became a selective process, prioritizing values of individualism and professional autonomy while framing the Soviet institutional context as merely a material, political, or economic “constraint” devoid of historical significance. To contextualise these findings, the article contrasts the narratives promoted by the competition with the historical realities and discourses it obscured, including Soviet postmodern and institutional critiques, the constraints and opportunities embedded in the state construction and financing system, and the forms of creativity available to architects within it.